Kérygme et imaginaire - Faessler, Marc (Apocrypha, 1996)
There is an essential difference between canonical and apocryphal texts. The comparison of John 20,11-18 with a short passage from the « Book of the Resurrection of Jesus Christ by Bartholomew the Apostle » (8.1-11.3) shows that the apocryphal text (in its hermeneutical status) loses the power of revelation constitutional of the canonical text (kerygmatic status).